Hemipotassium hemirubidium digallium(III) manganese(II) tris(phosphate) dihydrate - Zhang, Jing; Li, Ping; Liu, Zhi-Hong; Ng, Seik Weng (International Union of Crystallography, 2011)
The title manganese(II) substituted gallophosphate, K0.5Rb 0.5- [Ga2Mn(PO4)3(H 2O)2], features a three-dimensional network built of PO4 tetrahedra, GaO5 trigonal bipyramids and MnO 6 octahedra. The RbI and KI ions, which are disordered with respect to each other in a 1:1 ratio, occupy sites within the channels of the framework. The RbI/KI and MnII atoms occupy positions of 2 symmetry, as does one of the two P atoms. The RbI/KI site is surrounded by six O atoms [2.996 (2)-3.178 (4) Å] in an irregularly-shaped coordination environment. O-H⋯O hydrogen bonds between the water molecules and phosphate O atoms consolidate the crystal packing.